2001
DOI: 10.1016/s0092-8674(01)00294-x
|View full text |Cite
|
Sign up to set email alerts
|

Chimera Analysis of the Clock Mutation in Mice Shows that Complex Cellular Integration Determines Circadian Behavior

Abstract: The Clock mutation lengthens periodicity and reduces amplitude of circadian rhythms in mice. The effects of Clock are cell intrinsic and can be observed at the level of single neurons in the suprachiasmatic nucleus. To address how cells of contrasting genotype functionally interact in vivo to control circadian behavior, we have analyzed a series of Clock mutant mouse aggregation chimeras. Circadian behavior in Clock/Clock <--> wild-type chimeric individuals was determined by the proportion of mutant versus nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 68 publications
11
99
0
1
Order By: Relevance
“…Also, we found that individual variability in behavioural activity duration was related to properties evident at the population level, which is consistent with recent work investigating seasonal encoding within the SCN [29][30][31][32][33][34]. Of note, previous research also indicates a strong link between behavioural period and SCN function [35,36], but we were unable to address this issue here because our mice did not display marked variability in behavioural period.…”
Section: Discussionsupporting
confidence: 89%
“…Also, we found that individual variability in behavioural activity duration was related to properties evident at the population level, which is consistent with recent work investigating seasonal encoding within the SCN [29][30][31][32][33][34]. Of note, previous research also indicates a strong link between behavioural period and SCN function [35,36], but we were unable to address this issue here because our mice did not display marked variability in behavioural period.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the number of cells and the proportions of different cell types affect period and the stability of rhythms [8,19,12,18]. If functionally different cells are produced at different times, as the present results indicate [4], then small changes in the duration or intensity of proliferation of SCN progenitors at different times in development could be one source of variation (both within and between species) in the overall function of the nucleus.…”
Section: Discussionmentioning
confidence: 56%
“…From the invertebrate studies (for review see Dunlap 1996), rhythms result from transcriptional feedback loops in which the mRNA and protein products of circadian genes oscillate in abundance, with the mRNA and protein peaks offset. Mutant circadian-clock genes have been identified in hamsters and mice, and similar genetics may affect human rhythms (Ralph and Menaker 1988;Vitaterna et al 1994;Low-Zeddies and Takahashi 2001;Panda et al 2002a,b). Choline acetyltransferase and glutamate decarboxylase show circadian fluctuations in human subjects (Perry et al 1977), so the time of day at which death occurs may be pertinent (Lausson et al 1989).…”
Section: Circadian and Circannual Rhythmsmentioning
confidence: 99%